THE GREAT GREEN WALL PROJECT, FARMERS AND HERDERS CONFLICT IN PLATEAU STATE, NIGERIA - Abraham Abiodun Bamisile; Gloria Oduifa Otouaye (World Journal of Biology Pharmacy and Health Sciences, 2026)
The main cause of desertification in Sub-Saharan Africa has been climate change. Herdsmen, who frequently engage in persistent conflict with their host communities, particularly farmers, over the utilization of resources, land being foremost among them, are one of these migrant groups affected by the threat. The African Union (AU) launched the Great Green Wall Program (GGWP) in 2007 with the goal of building a green wall across Africa from the West to the East in order to regenerate the area and guarantee the livelihoods of the locals therein in response to the challenge posed by massive desertification in Africa as well as the inherent socio-economic disadvantages the menace carries. However, nine years after it was established, the initiative has not had a significant influence in some places, which has aided the cause of violence brought on by climate change in Nigeria. The purpose of this study was to evaluate the effectiveness of the Great Green Wall Project in Plateau State, Nigeria, in light of its anticipated value in reducing farmers/herders conflict. The survey research design was chosen for the study in order to meet the research objective. This research endeavor included both primary and secondary sources of data acquisition. The primary source of data was generated from farmers, herdsmen, members of staff of Ministry of Environment and Forestry, Nigeria Immigration Service and National Agency for the Great Green Wall via interview while the secondary source of data includes relevant text books, journals, publications, seminar papers, newspaper articles and other relevant materials. Content analysis was done on the primary data. The study found that even while the National Agency for the Great Green Wall has implemented a number of programs to address the threat of desertification, the agency urgently needed to expand its programs well beyond the eleven (11) frontier states that were most severely affected. The participation of all states in the federation in its initiatives will aid in easing and reducing the ongoing confrontations seen countrywide, particularly in Plateau state as it will aid in easing herders' migratory tendencies. In order to address the issue of foreign unchecked herders straying into the country, the study's conclusion emphasized the need for increased security at Nigeria's porous borders, particularly in the North, as well as the necessity of ongoing communication and understanding between herders, farmers, and local communities. In order to lessen ongoing conflicts, enhance border security for Nigeria, retain current grazing reserves, and teach farmers and herders conflict resolution skills, the management of conflict between herders and farmers must also involve the tool of conflict prevention. Thus, the main goal of this study is to examine the Great Green Wall Programme in light of how effective it is likely to be in reducing farmer and herder disputes in Plateau state, Nigeria.